The lethal effect of dimethoate on heart beat rate of female crab Brytelphusa guerini. - B, Deshai R; D, Shinde V; P, Katore B; E, Ambore N (Journal of Experimental Sciences, 2013)
The circulatory system is communicating organ system as it communicates with various systems of the body. It ensures proper distribution of the oxygen and nutrients apart from collection of metabolic waste and delivery to excretory organs like kidney. The circulatory body fluids transport various chemical substances necessary for metabolic continuity like hormones etc. The system of structures, consisting of the heart, blood vessels and blood is named as circulatory system. In these animals the system of cavities should be considered as a haemocoel and the blood which fulfils the characters of a circulatory fluid and those of inertial lymph should be caused haemolymph. The pigment haemocyanin is found in the blood of most crustaceans hence it has light blue color. The experimental animals collected from paddy field. The toxic effect of dimethoate resulted to disturb the regular working of heart. In this paper study about the heart rate of female crab. Barytelphusa guerini shows variations from 24 hr; 48 hr; 72 hr and 96 hours. The results are comparatively discussed with using graph and table.